Behaviour Analysis of Induction Motor Under Various Fault Conditions of Rotor bar at Different Loading - Sheokand, Kalpana; Turk, Neelam (International Journal of Computer Sciences and Engineering, 2025)
Induction motors have a vital influence in the protected and productive running of any modern plant. Faulty condition of these motors because of electrical and mechanical faults may antagonistically affect on line production and can cause unforeseen downtime. Along these lines, discovery of variations from the norm in the motor would maintain a strategic distance from exorbitant breakdowns and especially early location of early rotor bar faults are critical for productive activity of substantial induction motors. In this paper, execution of induction motor under 2D different failure’s modes like broken rotor bars are examined under different loading condition using FEM approach. Maxwell 2D Transient solver is utilized for breaking down the conductor of motor under solid and diverse faulty conditions.